Understanding autonomy and relationality in men's lives. (12th June 2022) - Elliott, Karla; Roberts, Steven; Ralph, Brittany; Robards, Brady; Savic, Michael
Abstract: Masculinities scholarship tends toward describing autonomy as bound up with hegemonic masculine ideals such as independence, atomization, and self‐sufficiency, without fully delving into the concept of autonomy. This article offers a more in‐depth conceptual treatment of autonomy, compared to its more simplified rendering in the literature on the dominant relational conceptualizations of masculinities. In doing so, we follow recent calls to avoid categorizing men according to typologies of masculinity, drawing instead on feminist theorizations of masculine autonomy and relationality to explore how both manifest in men's lives. We draw on a study of men's drinking practices, with our data coming from focus groups with 101 men in metropolitan and regional/rural Victoria, Australia; but the issues we attend to have relevance, and can be an impetus, for further scholarly thinking about autonomy in men's lives well beyond drinking practices, and in other similar industrialized nations. We explore how masculine autonomy remains an influential and harmful discourse, often impeding possibilities for men's greater intimacy, connection and care and reproducing gendered hierarchies. However, we simultaneously highlight how men are inescapably relationally situated, exposing masculine autonomy as a discursive ideal of valorized forms of masculinity rather than an achievable state in practice. We argue that acknowledging how men are relationally embedded and interdependent in practice offers potential avenues for further fostering men's care, intimacy and relationality, and might work toward ameliorating gendered inequalities that see care work and the work of sustaining relational networks disproportionately falling to women and marginalized men.